Cardiovascular and metabolic changes in insular infarcts: a delayed phenomenon? - Pasquini, M (BMJ Group, 2006)
Aggressive monitoring of electrocardiogram, blood pressure and blood glucose levels after 72 h in patients with insular infarcts is crucial in identifying whether they are prone to develop arrhythmias, hyperglycaemia and hypertension after the onset of stroke.